1989
DOI: 10.3109/00207458908987421
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity and Blood flow Velocity Changes: A Transcranial Doppler Study

Abstract: Seventy volunteers with no sign of cerebral vascular disease performed two series of 6 cognitive tasks, 3 of which are assumed to be processed predominantly by the left and 3 by the right hemisphere. During the tasks, blood flow velocity changes in the middle cerebral artery were recorded every 3 seconds by the transcranial Doppler method (TCD). All tasks increased blood flow velocities in both MCAs, but only the "right hemispheric" tasks resulted in a statistically significantly higher increase than the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 28 publications
5
34
1
2
Order By: Relevance
“…This is an issue that has been previously studied with TCD, using experimental designs that included visual stimuli with different degrees of complexity [29,30,31,32,33,34,35]. In this case, a simple visual perception task was selected, similar to that used in the study from Aaslid [29].…”
Section: Bfv Analysis During a Visual Perception Taskmentioning
confidence: 99%
See 4 more Smart Citations
“…This is an issue that has been previously studied with TCD, using experimental designs that included visual stimuli with different degrees of complexity [29,30,31,32,33,34,35]. In this case, a simple visual perception task was selected, similar to that used in the study from Aaslid [29].…”
Section: Bfv Analysis During a Visual Perception Taskmentioning
confidence: 99%
“…It is important to note that the BFV absolute or relative variations that can be observed during cognitive tasks are studied in most functional TCD works. However, and although the high temporal resolution of TCD is one of the key advantages of this technique, the instantaneous temporal evolution of BFV signals in subjects performing cognitive tasks has only been analyzed in some of the functional studies [20], which have found a maximum peak in BFV between 4 [180] to 20 s [181] after the initiation of a cognitive task, with an average peak after 6-9 s [31,158,149].…”
Section: 1 Bfv Signal Analysis In Functional Studiesmentioning
confidence: 99%
See 3 more Smart Citations